RE-OPERATIONS FOR BLEEDING IN CARDIAC SURGERY: TREATMENT STRATEGY - Gwozdziewicz, Marek; Olsak, Peter; Lonsky, Vladimir (Biomedical papers, 2008)
Aims: Cardiac surgery patients are prone to bleeding postoperatively owing to the extensive sternotomy wound, multiple vessel and heart sutures, and disorders of hemostasis. In this study we retrospectively analyzed the outcomes for all patients in our department who were re-operated for bleeding, over a 5 year period.Methods: A total of 4297 patients underwent heart surgery between February 2002 and January 2007, of which 98 (2.3 %) were emergency reoperations for bleeding. We analyzed the process of indication for repeat surgery, possible source of bleeding, and postoperative complications.Results: Most (85.7 %) of the reoperated patients had undergone their first operation as an elective cardiac procedure. The mean blood loss before the reoperation was 1557 ml. The studied group was characterized by increased mortality (11.2 %), longer ventilation period (35.1 hours) and ICU (4.5 days) and hospital (13.3 days) stays. The postoperative outcomes did not differ significantly between patients with TEG-detected coagulation disorder and the rest of the patients, or between patients treated with antilysin and those who did not receive antifibrinolytics.Conclusions: It is vital for the indication process leading to reoperation of the bleeding patient to be as short as possible so as to minimize the delay to repeat surgery. Echocardiography including ultrasound of both pleural spaces, and TEG could shorten that time delay, and should always be included when evaluating patients. Platelets should be administered more often, with the use of antifibrinolytics reserved for cases with confirmed fibrinolysis.
Keywords: Cardiac surgery/Postoperative bleeding/Cardiac tamponade